Acute Respiratory Distress in a Two-month-old Female - Conrad Krawiec; Caroline Perkowski (Oman Medical Journal, 2021)
Atwo-month-old female presented to the local emergency department with respiratory distress in the setting of a three-day history of febrile illness with symptoms of an upper respiratory infection. During initial evaluation, she was noted to be lethargic, tachycardic, and tachypneic.